An SROI analysis in measuring effectiveness of CSR Enduro entrepreneurship program of PT. Pertamina lubricants production unit Cilacap 2019-2021 - Pinkan, Dias Regian (Universitas Ahmad Dahlan, 2023)
CSR is a corporate responsibility program carried out with a social and business approach that is able to contribute to sustainable development for stakeholders or stakeholders. The sustainability contribution that can be made by companies to stakeholders can be in the form of economic, social and environmental benefits. This study aims to determine the social impact of the CSR program creating shared value that has been carried out by PT. Pertamina Lubricants Production Unit Cilacap in 2019-2021 and conducted an analysis using the social return on investment analysis knife. The type of research used is qualitative research with field research research methods. Every program carried out certainly aims to achieve something and have a positive impact on program targets. Likewise, this CSR program has economic, social and environmental impacts. This research has found out that the CSR Program carried by PT. Pertamina Lubricants, PU Cilacap brought the 1:5 comparison as the result calculated with SROI.